Strategy for Teaching Faith and Morals in Preventing Fear of Missing Out (FOMO) Among Madrasah Students - Delviyanti Ismail; Damhuri; Mariyaty Podungge; Abdul Sani; Abdul Karim (Journal of Practice Learning and Educational Development, 2026)
The rapid development of digital technology and social media has created new challenges for adolescent character formation, including fear of missing out (FOMO), a form of anxiety caused by the fear of being left behind in digital information, trends, or social activities. This study aims to describe the implementation of Akidah Akhlak learning, identify students' FOMO symptoms, analyze Akidah Akhlak learning strategies for preventing FOMO, and explain the supporting and inhibiting factors at Madrasah Aliyah Muhammadiyah Boliyohuto, Gorontalo Regency. This research employed a descriptive qualitative approach through field research. Data were collected through observation, interviews, and documentation involving 12 informants: the madrasah principal, an Akidah Akhlak teacher, and 10 eleventh-grade students. Data analysis consisted of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that Akidah Akhlak learning was implemented contextually by emphasizing responsibility, politeness, self-control, and wise use of social media. FOMO symptoms appeared in students' tendency to follow viral trends, anxiety when missing information, self-comparison through social media, and declining learning concentration. Teachers' strategies included discussion, question and answer, contextual lecturing, moral advice, motivation, religious habituation, and Islamic digital literacy reinforcement. Supporting factors included collaboration between teachers and the madrasah as well as religious programs, while inhibiting factors included the strong influence of social media, limited monitoring of gadget use outside school, and insufficient parental supervision. This study confirms that Akidah Akhlak learning has a strategic role as a moral foundation for students facing digital cultural pressures.